Beneficial effect of CETP gene polymorphism in combination with a Mediterranean diet influencing lipid metabolism in metabolic syndrome patients: CORDIOPREV study. Issue 1 (February 2018) - Garcia-Rios, Antonio; Alcala-Diaz, Juan Francisco; Gomez-Delgado, Francisco; Delgado-Lista, Javier; Marin, Carmen; Leon-Acuña, Ana; Camargo, Antonio; Rodriguez-Cantalejo, Fernando; Blanco-Rojo, Ruth; Quintana-Navarro, Gracia; Ordovas, Jose Maria; Perez-Jimenez, Francisco; et al.
Summary: The cholesteryl ester transfer protein (CETP) gene has been implicated in high-density lipoprotein (HDL-C) metabolism. However, little is known about the impact of this gene on metabolic syndrome (MetS) patients and its interaction with diet. Here, we evaluate whether the consumption of a Mediterranean diet, compared with a Low-fat diet, interacts with the rs3764261 SNP at the CETP locus to modify lipid metabolism in MetS patients. Plasma lipid concentrations and rs3764261 genotypes were determined in 424 MetS subjects participating in the CORDIOPREV clinical trial (NCT00924937). Gene-diet interactions were analyzed after a year of dietary intervention (Mediterranean diet (35% fat, 22% MUFA) vs Low-fat diet (28% fat, 12% MUFA)). We found significant gene–diet interactions between rs3764261 SNP and the dietary pattern for HDL-C ( P = 0.006) and triglyceride concentrations ( P = 0.040). Specifically, after 12 months of Mediterranean diet intervention, subjects who were carriers of the minor T allele (TT + TG) displayed higher plasma HDL-C concentrations ( P = 0.021) and lower triglycerides ( P = 0.020) compared with those who were homozygous for the major allele (GG). In contrast, in the Low-fat intervention group, no significant differences were found between CETP genotypes after 12 months of dietary treatment. Our data support the notion that the consumption of a Mediterranean diet may play a contributing role in triggering lipid metabolism by interacting with the rs3764261 SNP at CETP gene locus in MetS patients. Due to the complex nature of gene–environment interactions, dietary adjustment in MetS patients may require a personalized approach.